Studi Respon Fisiologis dan Kadar Gula Darah pada Tikus Putih (Rattus Norvegicus) yang Terpapar Streptozotocin (STZ) - Thatit Nurmawati (STIKes Patria Husada Blitar in collaboration with PPNI Kabupaten blitar, 2017)
Diabetes mellitus (DM) is a metabolic disorder with symptoms of polydipsi, polyuria, polyphagia, weight loss and tingling. The incidence of DM increased with the number of patients with type 2 DM more than type1 DM. Insulin resistance and deficiency is characteristic of type 2 diabetes. Streptozotocin (STZ) as a DM inducer model is better than alloxan by altering the physiological pancreas. The purpose of this study was to determine the physiological response and blood sugar levels of mice after exposure to STZ. Descriptive research design with the study subjects of 16 white wistar strains (Rattus norvegicus).  STZ is given 40mg / kg  BW for 3 days. Data collection is done 2 days after STZ last gift. Blood glucose  levels are obtained from  the end of the tail while the heart rate is measured  using a modified stethoscope. Data is presented in the mean ± SD. The results showed heart rate 500 ± 59.32 / min, weight 292,5 ± 65,26 (gr) and blood glucose content 237 ± 102.5 ml /dl. STZ responded to ratts resulting in physiological changes. Histologic observation of pancreatic cells is needed to determine the damage caused by STZ . Needed longer observation to see the response of ratts further.